Rehabilitating form, function and natural aesthetics with Onlay Ceramic IPS Empress Esthetic® : evidence and versatility = Rehabilitando forma, función y estética mediante el uso de un Onlay IPS Empress Esthetic® : evidencia y versatilidad - Ramírez Barrantes, Juan Carlos 1964- (2018)
Clinical research and in vitro laboratory tests have enabled the development and improvement of dental ceramics. Comprehension of the physical and mechanical properties of this material is essential, in order to ensure a functional, aesthetic and long-lasting posterior ceramic restoration. The clinical protocol for onlay preparation involves important considerations in treatment planning, such as selection of the restorative material, biomechanical design, color selection, dental substrates conditioning and adhesive cementation. This article discusses a brief review on the topic and a case presentation in which a posterior tooth was rehabilitated with an IPS Empress Esthetic® ceramic onlay.
La investigación clínica y las pruebas de laboratorio in vitro han permitido el desarrollo de los materiales cerámicos en odontología. La comprensión de las propiedades físicas y mecánicas de este material es esencial para asegurar una restauración funcional, estética y duradera. El protocolo clínico para la preparación de un onlay implica consideraciones importantes en la planificación del tratamiento, tales como la selección del material restaurador, diseño biomecánico, selección de color, acondicionamiento de sustratos dentales y cementación adhesiva. Este artículo discute una breve revisión sobre el tema y una presentación de caso en la que un diente posterior fue rehabilitado con una restauración indirecta tipo Onlay.
En revista Odóvtos, vol. 20, no. 2 (mayo-agosto 2018)
Descripción basada en el contenido visto 17 de julio, 2024
También disponible en formato HTML
Keywords: EMPASTES (ODONTOLOGIA); ESTETICA DENTAL; CERAMICA DENTAL